Ajankohtaista ja kiperää tiedekustantamisessa ja -julkaisemisessa : 17th Munin Conference on Scholarly Publishing - Nykyri, Susanna; Roinila, Markku (Informaatiotutkimus, 2023)
We discuss in this article the 17th Munin Conference on Scholarly Publishing which took place in Tromsø, Norway, end of 2022. The Munin Conference is an annual conference on scholarly publishing and communication, primarily revolving around open access publishing, open research data and open science. In the conference special focus was on copyright issues, including experiences on rights retention strategy, and on discussing open science infrastructures. We also reflect the flipped format-method used in the conference and the pre-workshop on publishing ethics. Non peer reviewed